PENGABDIAN KEPADA MASYARAKAT DALAM UPAYA MEMINIMALISIR POLUSI UDARA DI DESA CIMAUNG KECAMATAN CIKEUSAL KABUPATEN SERANG MELALUI KEGIATAN PENGHIJAUAN DAN PEMBUATAN PUPUK KOMPOS DARI DAUN KERING - Marini Magdalena; Eli Apud Saepudin (Yayasan Education and Social Center, 2023)
Currently in Indonesia is experiencing the dry season or summer because Indonesia only has two climates, namely the tropical climate and the subtropical climate, in the dry season a lot of leaves fall so that for the residents of Cimaung village, Cikeusal sub-district, Serang district, it is very annoying because they have to sweep the yard every morning which falls on dry leaves every day swept collected and burned, causing air pollution, usually mothers like to burn dry leaves at 06. 30 WIB even though in the morning the morning air is again good, because of the lack of education to community members about the dangers of air pollution so we uniba lecturers visited cimaung village to conduct socialization about the importance of maintaining a clean, beautiful environment away from pollution and the need to plant trees for reforestation and one more we uniba lecturers provide tips on how to collect dry leaves that can be processed into compost can be used as natural fertilizer for farmers